Fungsi Unit Layanan Disabilitas dalam Mendukung Pelaksanaan Pendidikan Inklusif - Ishartiwi Ishartiwi (Universitas Negeri Yogyakarta, 2023)
The existence of Disability Service Unit dan Resource Center of the Education, Youth and Sport Office in Yogyakarta (ULD-RC) in the implementation of inclusive education becomes an important part to facilitaterelated parties in seeking educational adjustments for students with special needs. However, in fact, ULD-RC is not yet known by the public and is still experiencing limited resources. This case study research explores stakeholders' understanding of students with special needs, expectations of ULD-RC, and its function in supporting inclusive education. The research subjects were 50 stakeholders involved inclusive education in Yogyakarta. Data collection used a questionnaire and was deepened by Focus Group Discussion (FGD). The questionnaire data were analyzed through quantitative descriptive techniques in the form of percentage calculations and qualitative descriptive for FGD data. The results showed that 70% of inclusive education stakeholders only understood physical characteristics and admitted that they were still confused about the diversity of characteristics for each type of special need. Some 42% of the subjects only understood the nature of inclusive education, but still did not understand the detailed requirements. Some 72% -97% of stakeholders hope that ULD-RC will clarify institutional positions, build service systems, design more flexible institutional structures, and clarify authorities. The results of stakeholder aspirations regarding the functions of ULD-RC include information functions, consulting services,identification and assessment, work skills into transition institutions, curriculum and learning program development, and inclusive school problem services.